An insect pest of the forest tree. (Hyphantrria cunea Drury) - Turner, Alonzo F. (My University, 1905)
Introduction: Hyphantria cunea Drury. Description:--Hyphantria cunea is one of the smaller of the Arctiidae. The average spread of the male adult is 24.86 millimeters; and of the female adult, 30.98 millimeters. There is considerable variation in the measurements for size in the species, as is evident from the table of measurements herewith given. The females are uniformly larger than the males, as will he observed from, the measurements given above. The color is in most cases a snow-white in our locality, especially the first brood of the season. From nearly two thousand moths matured in our insectary during the summer of 1904 1 failed to obtain out six specimens with more than a very smell dot, this located on the front margin of the fore wing at about one fourth of the distance to the tip. The six more spotted specimens have the second dot located at is the point where vein VII1 and. V3 unite. When a third dot appears, it located on the junction of vein V1 with vein III. The antennae vary from white to brownish, and the abdomen is usually snow-white—always so in my summer bred specimens. In the first spring brood, bred from specimens of my summer colonies, and kept over winter in the cages, I find specimens ranging from snow -white to very darkly spotted, the extremes of one brood being shown in the accompanying photograph
Two insect pests of the forest trees
Citation: Turner, Alonzo F. An insect pest of the forest tree. (Hyphantrria cunea Drury). Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Life History; Hyphantrria cunea Drury Damages; Remedies; Theses